Time Interaction With Two Spatial Dimensions: From Left/Right to Near/Far - Candini, Michela; D’Angelo, Mariano; Frassinetti, Francesca (Frontiers in Human Neuroscience, 2022)
We explore time and space relationship according to two spatial coding: the left/right extension and the reachability of stimulus along a near/far dimension. Four experiments were carried out in which healthy participants performed the Time and Spatial Bisection tasks in near/far space, before and after a short or long tool-use training. Stimuli were prebisected horizontal lines of different temporal durations in which the midpoint was manipulated according to Muller-Lyer illusion. The perceptual illusory effects emerged in spatial but not temporal judgments. We revealed that temporal and spatial representations dynamically change accordingly with individual’s action potentialities: temporal duration was perceived as shorter and the perceived line’s midpoint was shifted to the left in far than in near space. Crucially, this dissociation disappeared following a long but not short tool-use training. Finally, we observed age-related difference in spatial attention which may be crucial in built the memory temporal standard to categorize durations.